Processes that Contribute to Future South Asian Monsoon Differences in E3SMv2 and CESM2 - Gerald A. Meehl; Christine A. Shields; Julie M. Arblaster; John Fasullo; Nan Rosenbloom; Aixue Hu; Richard Neale; Antonietta Capotondi; Jean‐Christophe Golaz; Luke VanRoekel; H. Annamalai (Geophysical Research Letters)
Abstract Two Earth system models are analyzed to gain insight into the processes that govern projected changes in the South Asian monsoon. Warmer present‐day base state tropical SSTs contribute to coupled processes that produce greater future tropical Pacific warming in CESM2 with less of an increase in season‐mean monsoon precipitation compared to E3SMv2. This is attributed to changes in the large‐scale east‐west atmospheric Walker circulation, with relatively larger increases in precipitation and upper‐level divergence over the tropical Pacific and increases in upper‐level convergence over South Asia in CESM2. The stronger El Niño‐like response in CESM2, which increases Pacific precipitation and upper‐level divergence farther to the east, and larger future ENSO amplitude in E3SMv2, produce a greater relative increase in future monsoon‐ENSO connections in E3SMv2 compared to CESM2. This analysis indicates that the key processes that affect future monsoon‐ENSO connections are ENSO amplitude and size of the future tropical Pacific El Niño‐like response.